2018
DOI: 10.1128/jvi.01718-17
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy and Mitotic Cell Death Are Two Distinct HIV-1 Vpr-Driven Outcomes in Renal Tubule Epithelial Cells

Abstract: Given the emerging epidemic of renal disease in HIV+ patients and the fact that HIV DNA and RNA persist in the kidneys of HIV+ individuals despite therapy, it is necessary to understand the role of direct HIV-1 infection of the kidney. HIV-associated kidney disease pathogenesis is attributed in large part to viral proteins. Expression of vpr in renal tubule epithelial cells (RTECs) induces G2 arrest, apoptosis and polyploidy.The ability of a subset of cells to overcome the G2 block and progress to polyploidy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…Interestingly we observed four cellular fates for HIV-1 infected RTE cells: hypertrophy, cell death, proliferation and transcriptional silencing, consistent with viral latency. We have previously reported the presence of hypertrophic tubule cells in the Tg26 mouse model of renal infection and in HIVAN human biopsies, and demonstrated that this phenotype, together with cell cycle arrest and polyploidy are primarily induced by the expression of HIV-1 Vpr and its ability to impair cytokinesis [40][41][42]. The recapitulation of all those phenotypes in the in vitro model described here demonstrates that HIV-1 gene expression is responsible for the phenotypic changes observed in renal biopsies from HIV-1 infected individuals that correlated with renal dysfunction [5].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly we observed four cellular fates for HIV-1 infected RTE cells: hypertrophy, cell death, proliferation and transcriptional silencing, consistent with viral latency. We have previously reported the presence of hypertrophic tubule cells in the Tg26 mouse model of renal infection and in HIVAN human biopsies, and demonstrated that this phenotype, together with cell cycle arrest and polyploidy are primarily induced by the expression of HIV-1 Vpr and its ability to impair cytokinesis [40][41][42]. The recapitulation of all those phenotypes in the in vitro model described here demonstrates that HIV-1 gene expression is responsible for the phenotypic changes observed in renal biopsies from HIV-1 infected individuals that correlated with renal dysfunction [5].…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, at the suborganismal level, tissue stresses such as acute wounding or viral infection can induce polyploidy at the cellular level [6,7,[20][21][22][23], which can result in an increase in tissue mass via enlarged cells. This WGD response represents an alternative to generating new cells through cell division.…”
Section: Polyploidy As a Response To Acute Stressmentioning
confidence: 99%
“…hypertrophy, cell death, proliferation and transcriptional silencing, consistent with viral latency. We have previously reported the presence of hypertrophic tubule cells in the Tg26 mouse model of renal infection and in HIVAN human biopsies, and demonstrated that this phenotype, together with cell cycle arrest and polyploidy are primarily induced by the expression of HIV-1 Vpr and its ability to impair cytokinesis [40][41][42]. The recapitulation of all those phenotypes in the in vitro model described here demonstrates that HIV-1 gene expression is responsible for the phenotypic changes observed in renal biopsies from HIV-1 infected individuals that correlated with renal dysfunction [5].…”
Section: Discussionmentioning
confidence: 99%